THE INFLUENCE OF UPIN AND IPIN ANIMATION ON CHILDREN'S RELIGIOUS LIFE - Mohammad Jailani; Naufal Hafidh; Miftachul Huda (Penamas, 2023)
As we know, animation or cartooning is one of the most effective media to convey a message to children. It's the same with the Upin and Ipin series. This product from the neighboring country turns out to be not only entertaining but also implies a message and a mandate. Islam has taught that each of us is a brother and must remind each other of goodness. Upin and Ipin may be one of the media for da'wah if it can be easily conveyed, especially for children who are not yet baligh. The purpose of this study is to determine the effect of the animated series Upin and Ipin on the life of the Muslim religion for children because, more or less, television and the programs contained in it help children grow and develop. Through library studies based on several references and accompanied by surveys, Upin and Ipin turned out to have a good influence. They feel there is a moral message related to religion in the series.